Aktualisasi Kearifan Lokal dalam Pembangunan Daerah untuk Menciptakan Integrasi Bangsa Indonesia yang Berbudi Luhur - Nerson Nerson; Anang Puji Utama; Bayu Setiawan (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
The purpose of this study is to find out that Indonesia is one of the nation states that has a diverse social diversity of society. As a large unitary state, Indonesia requires special attention to development issues. Regional autonomy has encouraged regional development based on the participation of regional communities and the values of local wisdom. This paper aims to describe how to actualize the values of local wisdom in regional development in order to create the integrity of a virtuous nation. This research is a qualitative research with data collection using literature review. The results of this study show that regional development is part of Indonesia's national development. In addition, theactualization of the value of local wisdom in one region with another can have similarities can also be different. Furthermore, this study shows that there is a link between local wisdom, development and aspects of security defense, especially on peace issues and conflict resolution.